O ensino para crianças de 2 a 3 anos de idade na perspectiva histórico-crítica - Souza, Susyane Katlyn Thum de (2018)
The studies of Historical-Critical Pedagogy approach teaching as the guiding principle of Early Childhood Education, to promote integral development - from the perspective of Historical-Cultural Theory - and guarantee the educational rights of the young child. This study discusses the possibilities of accomplish this priority in front of the educational reality. The research was guided by the following problem: how can pedagogical practice with children of 2 and 3 years of age be able to overcome the predominant tendency of basic care and the application of punctual and non-systematized activities to an effective teaching practice that favors the integral development of the child? The study followed the objectives: Contribute to the understanding of teaching as the guiding principle of pedagogical work with young children; Identify potentialities and difficulties in the renewal of pedagogical practice in Early Childhood Education; To analyze the perceptions and practices, of Early Childhood professionals, in early childhood education. The course of this work consisted, initially, of carrying out a theoretical study on teaching in Early Childhood Education and converting its results into theoretical contents for a course of formation for teachers working in CMEIs in Foz do Iguaçu. The offer of this course was a methodological option to produce research data, through which it was tried to observe how the concepts and the guidelines studied would be understood and assimilated in practice by the teachers. The analysis consisted in verifying how the participants assimilated the contents, converted them into reflection to direct their plans and applied the planned practices. As well, analyzes the potentialities and difficulties of the pedagogical work with children from 2 to 3 years of age, ranging from the conception of adopted child development, to difficulties in organizing education, reaching issues such as education policies for Education And the need to rethink teacher training for this educational stage.